Maxillary Sinus Natural Killer/T-Cell Extranodal Lymphoma Mimicking a Dentoalveolar Abscess - Erika Antonia dos Anjos Ramos; Luciana Munhoz; Basílio Almeida Milani; Tomás Zecchini Barrese; Stephanie Kenig Viveiros; Emiko Saito Arita (Case Reports in Dentistry)
Extranodal natural killer/T-cell lymphoma (ENKL) is an aggressive and infrequent malignant neoplasm. Early sinonasal ENKL clinical symptomatology is often not specific which can mimic several clinical odontogenic processes such as dentoalveolar abscesses. A 41-year-old female was referred to our institution due to facial pain with skin rash, fever, and intraoral swelling in the left side of the maxillary region. Computed tomography (CT) revealed a soft tissue hypodense area in the left side with bone discontinuity in anterior and lateral maxillary sinuses. Initial laboratorial tests showed no alterations on hemogram, coagulation profile, and immune phenotype (CD3+/CD4+). However, the lesion progressed fastly showing an evident growth, so it was decided that an intraoral biopsy should be performed. The diagnosis was sinonasal ENKLs. This case is an example that the rare T-cell lymphoma can mimic an odontogenic lesion, thus puzzling the clinician. Fortunately, the rapid growth of the lesion prompted the correct diagnosis and early treatment.